Hepatoprotective effect of infliximab, an anti-TNF-? agent, on carbon tetrachloride-induced hepatic fibrosis - Bahcecioglu, Ibrahim Halil; Koca, Suleyman Serdar; Poyrazoglu, Orhan Kursat; Yalniz, Mehmet; Ozercan, Ibrahim Hanifi; Ustundag, Bilal; Isik, Ahmet (Springer/Plenum Publishers, 2008)
To assess the effect of infliximab, an anti-tumor necrosis factor (TNF)-alpha agent, on the carbon tetrachloride (CCl(4))-induced hepatic fibrosis in rats. Rats were randomized into three groups (n=9). The control group received only intraperitoneal (i.p.) olive oil. Hepatic fibrosis was induced by repeated i.p. injections of 1.5 ml/kg CCl(4) (1:3 mixture with olive oil) for 5 weeks in the remaining two groups which were also injected subcutaneous saline or 2 mg/kg infliximab. Infliximab reduced the levels of aspartate aminotransferase and alanine aminotransferase (p < 0.05 for both). The scores of hepatic necrosis, inflammation and fibrosis, and expression of alpha-smooth muscle actin were lower in the infliximab-treated group than the CCI(4)-treated group (p < 0.01, p < 0.001, p < 0.01, p < 0.001, respectively). However, there was no significant difference in terms of liver tissue and plasma malondialdehyde, and serum TNF-alpha levels, while infliximab relatively reduced the level of transforming growth factor-beta(1) (373.0 +/- 153.1 vs. 280.8 +/- 127.1 pg/ml). Treatment with infliximab attenuated the necro-inflammation and fibrogenesis in the CCI(4)-induced hepatic fibrosis, and thus it might be effective as a therapeutic anti-fibrotic agent.
Keywords: carbon tetrachloride; hepatic fibrosis; infliximab